Census of aquatic birds and conservation of wetlands in the high Andean slopes of Peru - Pulido Capurro, Victor (2021)
The experience of waterbird censuses in Peru started at the beginning of Century XXth with this kind of censuses made by the Peruvian Guano Company and then by IMARPE. Between 1992 and 2016, annual censuses have been conducted in 61 wetlands on 12 Peruvian departments, a total of 151 residents and migratories birds were registered. Censuses have contributed greatly to improve species of waterbirds knowledge and synergies among institutions and ornithologist that through volunteerism collect important data to the conservation of species and wetland management with particular reference to the high Andean slopes. The taxonomic composition of the species, the importance of the inventories, the migration routes of birds from the Nearctic, Austral and high Andean regions, and the protected areas in the conservation of wetlands and biodiversity are analyzed. The aim of this paper is to make a historical account of the censuses and their contribution to the knowledge of waterbirds carried out in the last three decades with special reference to the conservation of wetlands in the Andean slopes in Peru.